2019
DOI: 10.1055/s-0039-1697674
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Impairment at Two Years in Premature Infants with Prolonged Patency of Ductus Arteriosus after a Conservative Approach

Abstract: Objective The study aims to assess the impact on neurodevelopmental outcomes of a prolonged hemodynamically significant patent ductus arteriosus (PDA) after a conservative treatment. Study Design This involves the study of two cohorts of preterm infants 23 to 29 weeks gestation, before (n = 29) and after (n = 54) a conservative approach of PDA. We compared survival, major outcomes, and neurodevelopmental impairment (NDI) at 2 years and analyzed NDI in the conservative cohort according to the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, these interventions carry risks of short-and longterm adverse effects and complications (1-3). In addition, they might not reduce the risk of mortality and morbidities such as necrotizing enterocolitis, bronchopulmonary dysplasia (BPD), and neurodevelopmental impairment (4)(5)(6)(7)(8). Therefore, there have been growing calls for either abandoning routine interventions and/or more selective individualized interventions for PDA closure (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…However, these interventions carry risks of short-and longterm adverse effects and complications (1-3). In addition, they might not reduce the risk of mortality and morbidities such as necrotizing enterocolitis, bronchopulmonary dysplasia (BPD), and neurodevelopmental impairment (4)(5)(6)(7)(8). Therefore, there have been growing calls for either abandoning routine interventions and/or more selective individualized interventions for PDA closure (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment at or after 7 days was not associated with an increase in the risk of incidences of any morbidities. Long-term recent studies demonstrated that a conservative approach, even in the case of prolonged PDA, did not increase the risk of neurodevelopmental impairment ( 13 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite PDA's association with prematurity-related morbidities, no randomized controlled trial to date has demonstrated improvements in BPD, long-term neurodevelopmental outcomes or mortality after medical or surgical treatment of PDA (1,4,(9)(10)(11). Therefore, centers have been performing conservative follow-ups for PDA, especially since higher rates of spontaneous closure rates have been reported in the current era (12,13). A recent study that compared early routine treatment (ERT) of PDA with conservative management showed that ERT did not reduce either PDA ligations or the presence of a PDA at discharge, and did not improve secondary outcomes, However, ERT was associated with higher rates of late-onset sepsis (LOS) and death in infants born at >26 weeks of gestation (14).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, multicentre studies have reported a great variation in PDA-treatment rates among NICUs. 1,3 The effects of PDA treatment on long-term morbidity and mortality are being discussed controversially, 13,14,[17][18][19][20] which may partly explain the variation in treatment rates among NICUs worldwide.…”
Section: Discussionmentioning
confidence: 99%